The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1063/1.4804434
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed ZnO nanoparticle-based transistors via a room-temperature photochemical conversion process

Abstract: Articles you may be interested inEffects of hydrogen plasma treatment on the electrical behavior of solution-processed ZnO transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…We have previously shown that electron transport in ZnO-NPs TFTs is both a percolation and a trap-limited process dictated primarily by the poor inter-NPs coupling and the presence of surface trap states. 20 Recently, the passivation of these surface states has been achieved with the application of organic materials atop the metal oxide. [28][29][30] To investigate the potential of this approach, we deposited a PS layer atop the ZnO-NPs.…”
Section: Moreover the Hybrid Lamellar-like Channel Design Enables Inmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that electron transport in ZnO-NPs TFTs is both a percolation and a trap-limited process dictated primarily by the poor inter-NPs coupling and the presence of surface trap states. 20 Recently, the passivation of these surface states has been achieved with the application of organic materials atop the metal oxide. [28][29][30] To investigate the potential of this approach, we deposited a PS layer atop the ZnO-NPs.…”
Section: Moreover the Hybrid Lamellar-like Channel Design Enables Inmentioning
confidence: 99%
“…Looking beyond metal-salt precursors, which represent the state of the art in processing solution-based metal oxide TFTs, 10,12 suspensions of pre-formed nanomaterials, such as nanocrystals (NCs) or nanowires (NWs), are now emerging as promising candidates due to their long range crystallinity and potential for enhanced charge transport. 19,20 Moreover, pre-synthesized nanomaterials do not rely on high temperature annealing often used in conjunction with conventional metal-salt precursors for the in-situ synthesis of metal oxides, as well as for eliminating organic residues 10 that are known to deteriorate charge transport. 21 Despite the promising potential, however, the use of oxide nanomaterials in transistors faces significant challenges that extend beyond layer crystallinity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To study this effect we calculated the interface trap density (N tr ) and trap concentration (D tr , per unit area and unit energy) using the following equations: 55,56 …”
Section: Uv-vis Absorption Spectroscopymentioning
confidence: 99%
“…For example, Kwack and W.-S. Choi 2 and Kim et al 3 have reported solution-processed Zinc tin oxide (ZTO) TFTs with carrier mobilities of 4.9 and 6.0 cm 2 /Vs using a high temperature annealing processes at 300 C and 500 C, respectively. Much research is now focused on postdeposition processing as part of an effort to keep the temperature below 150 C. Indium zinc oxide (IZO) TFTs have achieved a mobility of 1.8 cm 2 /Vs by using high-pressure annealing (HPA) following thermal annealing at 220 C. 4 Similarly, UV light irradiation 5 and microwave-assisted annealing 6 have been adopted as useful post-deposition processes. Various passivation layers have also been used to reduce the effects of environmental factors, which lead to poor device stability.…”
mentioning
confidence: 99%